Prevention of Peer Violence by Implementing Teaching Contents - Example of Literature Instruction in Primary School - Snežana V. Božić; Marković R. Marija (University of Belgrade, Teacher Education Faculty, 2024)
The paper investigates the ways in which schools can contribute to the prevention of bullying, by gaining insight into a multi-layered structure of school activities that contributes to the positive effects of educational work on the development of students' personality and by pointing to the three levels of preventive action that can be carried out on an individual basis (universal, selective, and indicated prevention). Special emphasis is placed on universal prevention, given that science has proved that some school subjects (mother tongue and/or foreign language and literature, history, civic education, religious instruction, art and music lessons) and the extra-curricular activities related to them provide opportunities for this kind of bullying prevention. Focusing on literature instruction, we first look at its pedagogical role, linking the issue of bullying to humanistic and moral education. Literary texts that thematise this issue are very convenient for developing students' socio-emotional competencies, the competencies that are (also) directly linked to attitudes towards bullying and other forms of violence. "Deca" (Children), a short story by Ivo Andrić, stands out among such works represented in the literature curriculum for primary school. By applaying the emphatic-ethical model of reading, we investigate the pedagogical potential of this literary text, trying to point out the key "action" segments in the text which are activated only by a teacher's adequate methodological guidance of students during its collective interpretation.